A composite doped gas-sensitive material and its application in detecting nitrogen oxides

By comparing Pt and Sm composite doping of PrFeO3 material, the composite doping gas-sensitive material is prepared, which solves the problem of insufficient sensitivity and selectivity of existing NOx detection materials, and realizes efficient detection and low-temperature operation of low concentration NOx, reducing energy Consumption and false alarm rate.

CN118914301BActive Publication Date: 2025-01-10SHANDONG JIANZHU UNIV +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411398880.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-10
Estimated Expiration
2044-10-09

AI Technical Summary

Technical Problem

The sensitivity and selectivity of existing nitrogen oxide (NOx) detection materials are limited, especially for low concentration NOx detection, and the operating temperature is high, resulting in high energy consumption and low detection efficiency.

Method used

By comparing Pt and Sm to PrFeO3 material, the composite doped gas-sensitive material Xwt% Pt-SmyPr1-yFeO3 is prepared by sol-gel method to reduce the working temperature and improve the response speed and selectivity to NOx gas.

Benefits of technology

It realizes efficient detection of 1ppm NOx gas at 100-200°C, significantly reducing the working temperature, improving sensitivity and selectivity, reducing false alarms, and maintaining performance stability for long-term use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118914301B_ABST
    Figure CN118914301B_ABST
Patent Text Reader

Abstract

The present invention discloses a composite doped gas-sensitive material and its application in detecting nitrogen oxides, and relates to nitrogen oxide gas detection. The present invention prepares a composite doped gas-sensitive material Xwt% Pt-Sm by composite doping modification of Sm and Pt elements on PrFeO3 material. y Pr 1‑y FeO3, wherein Xwt% is the doping amount of Pt in the composite doped gas-sensitive material, 0.3%≤Xwt%≤5%, 0<y≤0.5. The present invention not only exhibits excellent sensitivity and selectivity to low-concentration nitrogen oxide gas through the composite doping design of Pt and Sm, but also reduces the working temperature of the composite doped gas-sensitive material, so that it can efficiently detect 1ppm nitrogen oxide gas at 100-200℃. The composite doped gas-sensitive material prepared by the sol-gel method has a simple preparation process and low cost, which is convenient for subsequent large-scale industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nitrogen oxide gas detection, and in particular to a composite doped gas sensitive material and an application thereof in detecting nitrogen oxides. Background Art

[0002] Nitrogen oxides (NO x ) is one of the main air pollutants, especially in motor vehicle exhaust and industrial waste gas. Long-term inhalation of NO x It may cause serious respiratory diseases and even endanger life. Therefore, how to detect NO efficiently and accurately x The concentration of pollutants has become one of the key topics in the field of environmental monitoring.

[0003] Currently, the most common x The gas sensor materials used for detection include metal oxide semiconductor materials, such as SnO2, ZnO and WO3, but ZnO has the problem of high detection temperature and poor selectivity, which leads to high energy consumption and is limited to the atmosphere environment; WO3 has the defect of long response-recovery time; SnO2 is a surface adsorption controlled gas sensitive material, and its specific surface area is an important factor affecting its performance. In order to improve its gas sensitive performance, it is often necessary to prepare materials with different microstructures, but the synthesis steps are relatively cumbersome. It can be seen that the sensitivity and selectivity of the above materials are limited, especially for low concentration NO x The detection is not ideal.

[0004] Perovskite materials are currently ideal materials for preparing gas sensors due to their advantages such as easy preparation and low cost. In the prior art, the paper "Preparation of LaFeO3 and PrFeO3 Nanofibers by Electrospinning and Study on Their Gas Sensing Properties" (Ma Lin, Northwest Normal University, 2018) discloses a method of preparing hollow structure PrFeO3 nanofiber samples by combining electrospinning and calcination. The optimal working temperature is 180°C and the minimum detectable acetone gas is 10ppm. 3+ Pei et al. (2021) disclosed the preparation of coral-shaped Sm-doped PrFeO3 nanocrystals by hydrothermal method. The response value of coral-shaped PrFeO3 nanocrystals to acetone gas at 270°C was 44.94-50ppm, and the lowest acetone gas that could be detected was 5ppm. 3+The response and recovery process of the PrFeO3 gas sensor can be improved. The PrFeO3 gas-sensitive materials prepared above all have good response and recovery to acetone gas, which is mainly achieved by constructing PrFeO3 gas-sensitive materials with different microstructures to increase the specific surface area, thereby improving their gas-sensitive performance. However, the working temperature of the PrFeO3 gas-sensitive materials prepared above is still relatively high, and they do not show good response speed and selectivity to nitrogen oxides.

[0005] Therefore, a composite doped gas-sensitive material was developed and used for NO x Gas detection to improve its NO x Improving the sensitivity, selectivity and response speed of gases, and lowering the operating temperature, are current research hotspots. Summary of the invention

[0006] In view of the above-mentioned prior art, the purpose of the present invention is to provide a composite doped gas-sensitive material and its application in detecting nitrogen oxides. The present invention obtains a composite doped gas-sensitive material by composite doping Sm and Pr on PrFeO3 material. Through the composite doping design of Pt and Sm, it can not only show excellent sensitivity and selectivity to low-concentration nitrogen oxide gas, but also reduce the working temperature of the composite doped gas-sensitive material, so that it can efficiently detect 1ppm nitrogen oxide gas at 100-200°C. The composite doped gas-sensitive material prepared by the sol-gel method has a simple and easy preparation process, low cost, and is convenient for subsequent large-scale industrial production, and is suitable for popularization and application.

[0007] To achieve the above object, the present invention adopts the following technical solution:

[0008] In a first aspect of the present invention, a composite doped gas-sensitive material is provided, wherein the molecular formula of the composite doped gas-sensitive material is Xwt% Pt-Sm y Pr 1-y FeO3, wherein Xwt% is the doping amount of Pt in the composite doped gas-sensitive material, 0.3%≤Xwt%≤5%, 0<y≤0.5.

[0009] Preferably, the composite doped gas-sensitive material has a uniformly dispersed nanoparticle structure with an average particle size of 70-150 nm.

[0010] A second aspect of the present invention provides a method for preparing a composite doped gas-sensitive material, comprising the following steps:

[0011] (1) Samarium nitrate, ferric nitrate, praseodymium trioxide, chloroplatinic acid and polyethylene glycol are mixed and dissolved in 8% to 9% by mass dilute nitric acid to obtain a mixed solution, and then chloroplatinic acid is added to the mixed solution and stirred for 5 to 10 hours to obtain a precursor solution;

[0012] The ratio of the added amounts of samarium nitrate, ferric nitrate, praseodymium trioxide, chloroplatinic acid, dilute nitric acid and polyethylene glycol is (0.01-3) mol: (0.01-3) mol: (0.01-3) mol: (0.01-50) g: (50-200) mL: (10-100) g;

[0013] (2) heating and stirring the precursor solution for 2-8 hours to obtain a sol material, calcining the sol material for 2-8 hours and then grinding it to obtain a composite doped gas-sensitive material;

[0014] The heating temperature is 40-80°C, and the calcination temperature is 600-1000°C.

[0015] Preferably, in step (2), the heating is water bath heating.

[0016] Preferably, in step (2), the stirring speed is 500-1000 r / min.

[0017] Preferably, in step (2), the grinding time is 3-8 hours.

[0018] The third aspect of the present invention provides the application of composite doped gas-sensitive materials, including the following 1) and / or 2):

[0019] 1) Detect nitrogen oxide gas;

[0020] 2) Preparation of nitrogen oxide gas sensors.

[0021] Preferably, the nitrogen oxide gas includes NO and NO2, and the concentration of the nitrogen oxide gas is 0.5-1.5 ppm.

[0022] A fourth aspect of the present invention provides a nitrogen oxide gas sensor, which is prepared by the following method:

[0023] The composite doped gas-sensitive material, deionized water and pine alcohol are mixed to obtain slurry; the slurry is spin-coated on the surface of a ceramic tube and, after aging, a nitrogen oxide gas-sensitive sensor is obtained.

[0024] Preferably, the added amount ratio of the composite doped gas-sensitive material, deionized water and pinene alcohol is (1-3) g: (3-9) mL: (1-3) mL.

[0025] Preferably, the ceramic tube is made of aluminum oxide.

[0026] Preferably, the spin coating speed is 600 rpm and the coating thickness is 80-200 μm.

[0027] Preferably, the aging temperature is 180-240° C., and the aging time is 16-24 h.

[0028] Beneficial effects of the present invention:

[0029] The present invention prepares a composite doped gas-sensitive material by composite doping PrFeO3 with Pt and Sm elements. The composite doped gas-sensitive material prepared is x ) gas detection shows excellent sensitivity and selectivity. Compared with traditional metal oxide gas-sensitive materials, the composite doped gas-sensitive material of the present invention can effectively distinguish NO x The present invention uses Pt and Sm elements to dope the composite gas-sensitive material, so that the composite doped gas-sensitive material can detect 1ppm nitrogen oxide gas, which has a synergistic effect in improving the sensitivity and selectivity of low-concentration nitrogen oxide detection.

[0030] The present invention adopts Pt and Sm composite doping design to enable the gas-sensitive material to achieve NO in the lower temperature range of 100-200°C. x The efficient detection of gas significantly reduces the operating temperature of the gas sensor. This not only saves energy, but also increases the service life and stability of the sensor. In addition, the composite doped gas-sensitive material prepared by the present invention has stable performance and small sensitivity loss during long-term use, and can maintain reliable gas detection performance under different environmental conditions.

[0031] The composite doped gas-sensitive material prepared by the sol-gel method has a simple preparation process, is easy to operate, has low cost, is convenient for subsequent large-scale industrial production, and is suitable for popularization and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 : XRD pattern of the composite doped gas-sensitive material prepared in Example 1;

[0033] Figure 2 : SEM image of the composite doped gas-sensitive material prepared in Example 1;

[0034] Figure 3 : EDS image of the composite doped gas-sensitive material prepared in Example 1;

[0035] Figure 4 : A graph showing the relationship between the gas-sensing performance of the composite doped gas-sensitive material prepared in Example 1 and the gas-sensitive materials prepared in Comparative Examples 1-3 to 1 ppm NO gas and temperature;

[0036] Figure 5 : A graph showing the relationship between the gas-sensing performance of the composite doped gas-sensitive material prepared in Example 1 and the gas-sensitive materials prepared in Comparative Examples 1-3 to 1 ppm NO2 gas and temperature;

[0037] Figure 6: Schematic diagram of the response of the composite doped gas-sensitive material prepared in Example 1 to multiple gases at 1 ppm. DETAILED DESCRIPTION

[0038] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.

[0039] Nitrogen oxides are one of the air pollutants, which are mostly produced by motor vehicle exhaust and industrial waste gas. Long-term inhalation can cause respiratory diseases. In the prior art, the gas-sensitive materials used to detect nitrogen oxides are metal oxide semiconductor materials, but they have limited sensitivity and selectivity, and the operating temperature is too high, especially for low-concentration NO x The detection is not ideal.

[0040] Based on this, the present invention uses Sm and Pt elements to composite-dope PrFeO3 materials to obtain composite-doped gas-sensitive materials Xwt% Pt-Sm y Pr 1-y FeO3, wherein Xwt% is the doping amount of Pt in the composite doped gas-sensitive material, 0.3%≤Xwt%≤5%, 0<y≤0.5.

[0041] The present invention uses the noble metal Pt to modify the PrFeO3 material, which can not only change the potential barrier on the surface of the PrFeO3 material, thereby changing the initial resistance of the material, but also improve the activity of gas molecules, enhance the degree of redox reaction and increase the reaction rate, so that the composite doped gas-sensitive material has higher responsiveness, selectivity and shorter response-recovery time to nitrogen oxide gas. By doping with the rare earth element Sm, the internal lattice shape of the PrFeO3 material can be changed, causing defects, thereby affecting the electrochemical properties of the material.

[0042] The present invention prepares a composite doped gas-sensitive material of Pt and Sm by a sol-gel method, and the prepared composite doped gas-sensitive material has a uniformly dispersed nanoparticle structure, and its average particle size is 70-150nm. When the grain size is close to or less than the Debye length of the sensor material, the grain size will significantly affect the gas-sensitive performance of the sensor material, and rare earth doping will greatly reduce the grain size of the sample, which is beneficial to the gas-sensitive response. The smaller the particle size of the material, the larger the relative specific surface area, and more adsorption sites can be provided to the target gas. The surface of the material can adsorb more target gas to produce a corresponding more intense redox reaction; the more pores, the more transport channels provided to the target gas, which can also intensify the corresponding redox reaction of the target gas on the surface of the material, so that the material exhibits better gas-sensitive performance.

[0043] The present invention performs Pt and Sm doping modification on praseodymium ferrite material to obtain a composite doped gas-sensitive material that can be used to detect 1 ppm nitrogen oxide gas, and the doping modification by combining Pt and Sm has a synergistic effect in improving the sensitivity and selectivity of low-concentration nitrogen oxide detection.

[0044] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.

[0045] The experimental materials used in the embodiments of the present invention are all conventional experimental materials in the art and can be purchased through commercial channels.

[0046] Example 1: 1wt% Pt-Sm 0.1 Pr 0.9 Preparation of FeO3 composite doped gas sensitive materials

[0047] (1) 3.364 g of samarium nitrate, 24.185 g of ferric nitrate, 29.682 g of praseodymium trioxide, 0.664 g of chloroplatinic acid and 50 g of polyethylene glycol were mixed and dissolved in 80 mL of 8.5% dilute nitric acid to obtain a mixed solution, which was stirred for 2 h to obtain a precursor solution;

[0048] (2) The precursor solution was heated to 80°C in a water bath and stirred at 1000 r / min for 4 h to obtain a sol material. The sol material was calcined at 850°C for 6 h to completely burn out the hydrocarbons in the sol material. After cooling to room temperature, it was ground for 6 h to obtain 1wt% Pt-Sm 0.1 Pr 0.9 FeO3 composite doped gas sensitive material, the particle size of the composite doped gas sensitive material is 60-100nm.

[0049] Example 2: 2wt% Pt-Sm 0.2 Pr 0.8 Preparation of FeO3 composite doped gas sensitive materials

[0050] (1) Mix 6.728 g of samarium nitrate, 24.185 g of ferric nitrate, 26.384 g of praseodymium trioxide, 1.328 g of chloroplatinic acid and 60 g of polyethylene glycol, dissolve in 80 mL of 8.5% dilute nitric acid to obtain a mixed solution, and stir for 4 h to obtain a precursor solution;

[0051] (2) The precursor solution was heated to 60°C in a water bath and stirred at 500 r / min for 6 h to obtain a sol material. The sol material was calcined at 750°C for 6 h to completely burn out the hydrocarbons in the sol material. After cooling to room temperature, it was ground for 6 h to obtain 2 wt% Pt-Sm 0.2 Pr 0.8 FeO3 composite doped gas sensitive material.

[0052] Example 3: 3wt% Pt-Sm 0.3 Pr 0.7 Preparation of FeO3 composite doped gas sensitive materials

[0053] (1) 10.092 g of samarium nitrate, 24.185 g of ferric nitrate, 23.086 g of praseodymium trioxide, 1.992 g of chloroplatinic acid and 70 g of polyethylene glycol were mixed and dissolved in 80 mL of 8.5% dilute nitric acid to obtain a mixed solution, which was stirred for 8 h to obtain a precursor solution;

[0054] (2) The precursor solution was heated to 60°C in a water bath and stirred at 500 r / min for 8 h to obtain a sol material. The sol material was calcined at 750°C for 6 h to completely burn out the hydrocarbons in the sol material. After cooling to room temperature, it was ground for 6 h to obtain 2 wt% Pt-Sm 0.2 Pr 0.8 FeO3 composite doped gas sensitive material.

[0055] Example 4: 0.3wt% Pt-Sm 0.1 Pr 0.9 Preparation of FeO3 composite doped gas sensitive materials

[0056] (1) 3.364 g of samarium nitrate, 24.185 g of ferric nitrate, 29.682 g of praseodymium trioxide, 0.1992 g of chloroplatinic acid and 55 g of polyethylene glycol were mixed and dissolved in 80 mL of 8.5% dilute nitric acid to obtain a mixed solution. Then, chloroplatinic acid was added to the mixed solution and stirred for 5 h to obtain a precursor solution.

[0057] (2) The precursor solution was heated to 40°C in a water bath and stirred at 500 r / min for 8 h to obtain a sol material. The sol material was calcined at 600°C for 2 h to completely burn out the hydrocarbons in the sol material. After cooling to room temperature, the sol material was ground for 3 h to obtain 0.3 wt% Pt-Sm 0.1 Pr 0.9 FeO3 composite doped gas sensitive material.

[0058] Example 5: 5wt% Pt-Sm 0.5 Fe 0.5Preparation of O3 composite doped gas sensitive materials

[0059] (1) 16.82 g of samarium nitrate, 24.185 g of ferric nitrate, 16.49 g of praseodymium trioxide, 3.32 g of chloroplatinic acid and 50 g of polyethylene glycol were mixed, dissolved in 8.5% dilute nitric acid to obtain a mixed solution, and stirred for 10 h to obtain a precursor solution;

[0060] (2) The precursor solution was heated to 80°C in a water bath and stirred at 1000 r / min for 6 h to obtain a sol material. The sol material was calcined at 1000°C for 8 h to completely burn out the hydrocarbons in the sol material. After cooling to room temperature, the sol material was ground for 8 h to obtain 5 wt% Pt-Sm 0.5 Fe 0.5 O3 composite doped gas sensitive material.

[0061] Example 6: Preparation of nitrogen oxide gas sensor

[0062] The 1wt% Pt-Sm 0.1 Pr 0.9 FeO3 composite doped gas sensitive material, deionized water and pine oil were mixed in the ratio of 1g:3mL:1mL to obtain slurry, which was spin-coated on the surface of aluminum oxide ceramic tube at a speed of 800rpm to make the coating thickness of 109μm. The tube was aged at 200℃ in air for 24h to obtain nitrogen oxide gas sensitive sensor.

[0063] Comparative Example 1:

[0064] The difference between this comparative example and Example 1 is that in step (1), samarium oxide and chloroplatinic acid are not added, and the obtained gas-sensitive material is PrFeO3.

[0065] Comparative Example 2:

[0066] The difference between this comparative example and Example 1 is that in step (1), no samarium oxide is added, and the obtained gas-sensitive material is 1 wt% Pt-PrFeO3.

[0067] Comparative Example 3:

[0068] The difference between this comparative example and Example 1 is that in step (1), no chloroplatinic acid is added, and the gas-sensitive material obtained is Sm 0.1 Pr 0.9 FeO3.

[0069] Test Example 1: Structural Characterization

[0070] The 1wt% Pt-Sm prepared in Example 1 0.1 Pr 0.9The structure of FeO3 composite doped gas sensitive materials was characterized. Figure 1-Figure 3 shown.

[0071] Figure 1 is the XRD pattern of the prepared composite doped gas-sensitive material. Figure 1 It can be seen that the crystallization peaks correspond to the (111), (112) and (021) phases of PrFeO3 (No. 47-0065). Figure 2 The SEM images of the prepared composite doped gas-sensitive material at 30K, 60K and 100K magnifications are shown in Figure 2. Figure 2 It can be seen that the composite doped gas-sensitive material presents a typical nanoparticle structure, the material has a large specific surface area and porosity, and there are more reaction sites and transmission channels for gas molecules. Figure 3 This is the EDS image of the prepared composite doped gas-sensitive material. Figure 3 It can be seen that Pt and Sm elements exist in the prepared composite doped gas-sensitive material.

[0072] Test Example 2: Gas Sensing Performance Test

[0073] The composite doped gas-sensitive material prepared in Example 1 and the gas-sensitive materials prepared in Comparative Examples 1-3 were coated on the sensing film to detect the gas-sensitive response (Rg / Ra). Ra is the resistance of the sensor in the air, and Rg is the resistance of the gas being measured. The experimental environment is: RH is 20%, and the ambient temperature is 20°C.

[0074] Figure 4 The graph is a relationship between the response of the composite doped gas-sensitive materials prepared in Examples 1-3 and Example 1 to 1 ppm NO gas and temperature. Figure 4 It can be seen that the optimal working temperature of the composite doped gas-sensitive material prepared by the present invention is 160°C. At a working temperature of 160°C, the gas-sensitive response of the composite doped gas-sensitive material prepared by the present invention is 7.32, while the gas-sensitive response value of the gas-sensitive material PrFeO3 prepared in Comparative Example 1 is 1.93, the gas-sensitive response value of the composite doped gas-sensitive material obtained by only using Pt to dope modified PrFeO3 in Comparative Example 2 is 2.16, and the gas-sensitive response value of the composite doped gas-sensitive material obtained by only using Pt to dope modified PrFeO3 in Comparative Example 3 is 4.72. It can be seen that the present invention has a synergistic effect in improving the response of the composite doped gas-sensitive material to 1ppmNO gas by composite doping of Pt and Sm on PrFeO3 material.

[0075] Figure 5 The graph is a relationship between the response of the composite doped gas-sensitive materials prepared in Examples 1-3 and Example 1 to 1 ppm NO2 gas and temperature. Figure 5It can be seen that the optimal working temperature of the composite doped gas-sensitive material is 130°C. At a working temperature of 130°C, the gas-sensitive response of the composite doped gas-sensitive material prepared by the present invention is 8.93, while the gas-sensitive response value of the gas-sensitive material PrFeO3 prepared in Comparative Example 1 is 2.34, the gas-sensitive response value of the composite doped gas-sensitive material obtained by only using Pt for doping modification in Comparative Example 2 is 2.56, and the gas-sensitive response value of the composite doped gas-sensitive material obtained by only using Pt for doping modification in Comparative Example 3 is 6.22. It can be seen that the present invention has a combined synergistic effect in improving the response of the composite doped gas-sensitive material to 1ppmNO2 gas by composite doping of Pt and Sm on the PrFeO3 material.

[0076] Figure 6 FIG. 1 is a schematic diagram showing the response of the composite doped gas-sensitive material prepared in Example 1 to 1 ppm of various gases. Figure 5 It can be seen that when exposed to various gases, the 1wt% Pt-Sm 0.1 Pr 0.9 The selectivity of FeO3 to NO and NO2 nitrogen oxide gases is higher than that to other gases such as CO and CO2. It can be seen that the gas-sensitive material prepared by the present invention has good selectivity to nitrogen oxides.

[0077] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. Application of a composite doped gas-sensitive material in detecting nitrogen oxide gas, characterized in that: The molecular formula of the composite doped gas-sensitive material is Xwt% Pt-Sm y Pr 1-y FeO3, wherein Xwt% is the doping amount of Pt in the composite doped gas-sensitive material, 0.3%≤Xwt%≤5%, 0<y≤0.5; The composite doped gas-sensitive material is prepared by the following method: (1) Samarium nitrate, ferric nitrate, praseodymium trioxide, chloroplatinic acid and polyethylene glycol are mixed and dissolved in 8% to 9% by mass dilute nitric acid to obtain a mixed solution, and then chloroplatinic acid is added to the mixed solution and stirred for 5 to 10 hours to obtain a precursor solution; The ratio of the added amounts of samarium nitrate, ferric nitrate, praseodymium trioxide, chloroplatinic acid, dilute nitric acid and polyethylene glycol is (0.01-3) mol: (0.01-3) mol: (0.01-3) mol: (0.01-50) g: (50-200) mL: (10-100) g; (2) The precursor solution is heated at 40-80°C and stirred for 2-8 hours to obtain a sol material. The sol material is calcined at 600-1000°C for 2-8 hours and then ground to obtain a composite doped gas-sensitive material.

2. The use according to claim 1, characterized in that The average particle size of the composite doped gas-sensitive material is 70-150 nm.

3. The use according to claim 1, characterized in that The nitrogen oxide gas includes NO and NO2, and the concentration of the nitrogen oxide gas is 0.5-1.5 ppm.

Citation Information

Patent Citations

  • Gas-sensing material with noble metal doped composite metal oxide and its production

    CN1746131A